The effectiveness of David procedure for aneurysm of the root and ascending part of the aorta - O.V. Zelenchuk; B.M. Todurov; I.O. Stetsiuk; V.B. Demyanchuk; D.O. Loskutov; N.O. Yashchenko; N.V. Ponych (Кардіохірургія та інтервенційна кардіологія)
The aim – comparison of the results of David and Bentall operations in patients with aneurysms of the root and ascending aorta. Materials and methods. The one-centre study included 85 patients who underwent planned and urgent surgical treatment from 2019 to 2022. The patients were divided into two groups depending on the type of surgical intervention: the Bentall procedure was performed in the I group, while the David procedure was performed in the II group. Results. The study did not determine statistically significant differences in such indicators as the duration of artificial blood circulation and the time of aortic clamping. No significant differences were found in the duration of artificial lung ventilation and stay in the intensive care unit. However, the total length of hospital stay in the group of patients with David procedure was statistically lower and was 17.3 (8–35) days, while in the group with Bentall operation it was 23.7 (10–40) days (p = 0.01). The results of our analysis show that the early postoperative clinical results of the David and Bentall procedures are good and there are no significant differences. During David procedure, a statistically significant positive result of surgical treatment was revealed by such an indicator as the degree of insufficiency on the aortic valve (before and after the operation, 2.7 ± 1.3 and 0.8 ± 0.6, respectively, p < 0.05). In addition to the above indicator, significant results were found in the indicators: left ventricular end-diastolic size and left ventricular end-diastolic volume. Conclusions. The good immediate results of Bentall and David operations suggest that surgical repair of ascending and aortic root aneurysms using these operations can be equally safe when performed according to absolute anatomical indications and by an experienced surgical team. If both operations might be used in a particular patient, the valve-sparing operation should be preferred, given the lower risk of postoperative complications associated with the presence of a mechanical or biological prosthesis (such as thromboembolism, bleeding associated with anticoagulants, and structural deterioration of the bioprosthesis).